Art and science in word and image : exploration and discovery - Williams, Keith, 1958-; Aymes-Stokes, Sophie; Baetens, Jan (Word & image interactions, 2019)
Art and Science in Word and Image investigates the theme of 'riddles of form', exploring how discovery and innovation have functioned inter-dependently between art, literature and the sciences. Using the impact of evolutionary biologist D'Arcy Thompson's On Growth and Form on Modernist practices as springboard into the theme, contributors consider engagements with mysteries of natural form in painting, photography, fiction, et cetera, as well as theories about cosmic forces, and other fields of knowledge and enquiry. Hence the collection also deals with topics including cultural inscriptions of gardens and landscapes, deconstructions of received history through word and image artworks and texts, experiments in poetic materiality, graphic re-mediations of classic fiction, and textual transactions with animation and photography. Contributors are: Dina Aleshina, Márcia Arbex, Donna T. Canada Smith, Calum Colvin, Francis Edeline, Philippe Enrico, Étienne Février, Madeline B. Gangnes, Eric T. Haskell, Christina Ionescu, Tim Isherwood, Matthew Jarron, Philippe Kaenel, Judy Kendall, Catherine Lanone, Kristen Nassif, Solange Ribeiro de Oliveira, Eric Robertson, Frances Robertson, Cathy Roche-Liger, David Skilton, Melanie Stengele, Barry Sullivan, Alice Tarbuck, Frederik Van Dam.